1997
DOI: 10.1002/(sici)1096-9063(199708)50:4<331::aid-ps602>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

α-Hydroxyarylacetamides: A New Class of Fungicidally Active Compounds

Abstract: The synthesis and subsequent discovery of fungicidally active a-hydroxyarylacetamides originated from a report that phenyltartronic acid amides exhibited insecticidal activity.1 The slow-acting nature of this activity led us to speculate that these compounds might be metabolically activated via hydrolysis and then decarboxylation of one of the amide moieties. Subsequently, a synthesis programme looking at a wide range of ahydroxy-arylacetamides was instigated. This yielded, not a new insecticide, but a novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Mandelamides bearing a 3,4-dioxy-substituted phenethylamine as amine part have been known for almost 10 years to be active against oomycetes diseases. 5,6 In this paper we have demonstrated that the introduction of propargyloxy functions into the benzylic position of the mandelic acid moeity and into the para position of the phenethylamine leads to an enormous increase in fungicidal efficacy. Mandipropamid (5), the development compound selected on the basis of the in-depth optimisation study, displays outstanding activity against late blight diseases of potato and tomato (P. infestans), combined with excellent efficacy on downy mildew diseases of grape (P. viticola) and cucumber (Pseudoperonospora cubensis Rostow).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Mandelamides bearing a 3,4-dioxy-substituted phenethylamine as amine part have been known for almost 10 years to be active against oomycetes diseases. 5,6 In this paper we have demonstrated that the introduction of propargyloxy functions into the benzylic position of the mandelic acid moeity and into the para position of the phenethylamine leads to an enormous increase in fungicidal efficacy. Mandipropamid (5), the development compound selected on the basis of the in-depth optimisation study, displays outstanding activity against late blight diseases of potato and tomato (P. infestans), combined with excellent efficacy on downy mildew diseases of grape (P. viticola) and cucumber (Pseudoperonospora cubensis Rostow).…”
Section: Resultsmentioning
confidence: 95%
“…The hydroxy function of the mandelic acid moiety of 10 can be alkylated with activated alkyl halides. Thus the introduction of a second propargyl group leads to mandipropamid (5), which can also be prepared by direct coupling of 6 with 4-chloromandelic acid and subsequent double propargylation.…”
Section: Materials and Methods 21 Chemical Synthesismentioning
confidence: 99%
See 3 more Smart Citations